Policy influencer support for active transportation policy in two Canadian provinces: Implications for advocacy. (January 2023) - Molner, Brittany; Curtin, Kimberley D.; Kongats, Krystyna; Brown, Jennifer Ann; Thomson, Mathew; Atkey, Kayla; Nykiforuk, Candace I.J.
Abstract: Introduction: Active travel or transportation (AT) is recognized for its growing potential to improve the health and wellbeing of Canadians. AT policy helps to promote active commuting by reducing barriers, such as through the development of infrastructure and reducing traffic. As policy influencers are important gatekeepers who can promote or impede policy, this research explores policy influencer support for AT policy in two Canadian provinces. Methods: The Chronic Disease Prevention Survey has examined policy influencer and general public support for healthy public policy options since 2009. The 2019 iteration surveyed policy influencers in Alberta (n = 248) and Manitoba (n = 115) working in government and non-government organizations. These policy influencers were asked to indicate their level of support for eight AT policy options and demographic information. Descriptive statistics were used to analyze support for AT policy options and demographics. Different levels of support between policy influencers by province and group were determined by a two-sided Pearson's chi-squared test. Results: Respondents indicated high levels of support across all policy influencer groups. Four policy options demonstrated significantly lower support among Alberta respondents compared to Manitoba. Respondents in government and non-government groups reported similar levels of support for all but one policy option ( Ensure municipalities establish minimum standards for health promoting environments that developers need to address; 78.3% vs. 91.2% respectively ). Overall levels of support for active school transportation were high across respondent groups ( average 96.0% ). Conclusions: By understanding the current levels of support, advocates can appropriately garner support and tailor advocacy plans. Key takeaways: (1) school-based policies could be a quick win for AT advocates and (2) work is needed to build support for more intrusive but impactful AT policy options. Overall, the high levels of support by policy influencer respondents across most AT policy options indicate a potential policy window for advocates. Highlights: The Chronic Disease Prevention Survey examined support for healthy public policy options, including AT policy. Respondents across all policy influencer groups had high levels of support for AT policies, particularly school-based. More restrictive policy options received lower support from Alberta-based respondents. Healthy public policy advocates may capitalize on the current policy window to implement AT polices and infrastructure.